Traits of weed species present in maize respond to tillage and cropping systems - Bensch, Johanna; Pannwitt, Heike; Gerowitt, Bärbel (Frontiers in Agronomy, 2023)
Arable weeds adapt to any changes in disturbance and management. On arable fields, tilling disturbs the soil while cropping practices like rotation, pesticide use, fertilizer use, and the use of subsidiary crops characterize the management of the field. On a species level, weeds adapt in their abundance and composition. The species have certain traits to use the on-site resources best. Our objective was to investigate if traits beyond just species describe the adaptation of weeds to tillage and cropping systems. Therefore, we present a use-case of weeds on fields cropped with maize in Germany. Over two years, we conducted a nationwide weed survey on 577 maize fields. On each field, the abundance of each weed species was counted on ten randomly sampled square plots of 0.1 m² not treated with herbicides at the fourth to eighth leave stages of the maize. Weed species frequent on at least 5 % of the fields were assigned traits. Traits were taken from published, updated databases. We interviewed all farmers about the management practices of their fields. The management practice data identified three management clusters of tillage and cropping sequence on maize fields. The standard system so far is a management system characterized by inversion tillage and maize cropped in rotations (“Traditional”). The two transformation systems are maize cropped in rotations but with non-inversion tillage as the method of soil disturbance (“Conservational”) and maize cropped continuously regardless of the tillage system (“Monoculture”). Ordination techniques showed that both weed species and traits are assigned to these management systems. Traditional disfavored weed species with a greater plant height. Conservational selected dicot weed species with a high seed weight and a long flowering duration. Monoculture mainly filtered monocot weed species and favored weeds that germinate in spring. Our study describes weed responses on transformations of maize cropping in tillage and cropping systems on both the species and the trait level. This application expresses the importance and value of collecting weed surveys with field management data on a geographically wide-spread and repeated time scale.